The grandmaster : Magnus Carlsen and the match that made chess great again - Butler, Brin-Jonathan (Simon & Schuster Nonfiction Original Hardcover, 2018)
"A firsthand account of the dramatic 2016 World Chess Championship between Norway's Magnus Carlsen and Russia's Sergey Karjakin, which mirrored the world's geopolitical unrest"--Publisher marketing.